PIPE STRESS ANALYSIS ON THE RIVER CROSSING PIPELINE WITH HORIZONTAL DIRECTIONAL DRILLING (HDD) AS CONSTRUCTION METHOD CASE STUDY: OIL PIPELINE TEMPINO PLAJU KM 3 - IBNU SINA (NIM : 13104015); Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, MOCHAMAD
Onshore pipeline sometimes must cross river, swamp, highway, railway or a residential settlement. Horizontal Directional Drilling is one of the method that is used to install the pipa in this condition. HDD was conducted using 3 stages, Drilling Pilot Hole, Expanding Pilot Hole dan Pull Back The Pipe. Stress analysis on the pipe needs to be done so we know the pipe condition as the result of the loads that works on it. In this final project, stress analysis on the pipe was conducted using software Nastran for Windows v4.5. The stress that are analyzed are caused by the axial load on the beginning of the installation, the bending loads, and the loads that happens because of the internal pressure on operation and hydrostatic condition. Variation on the value of the several installation parameters are also done to get the pipe stress on many conditions. As a study case, we analyze the stress on the pipe that crossing Gerong River with the size NPS 10Ã‚Â” schedule 40. From the analysis, the maximum stress on trajectory condition will happen because of the combination between axial load and bending load, with the stress value is 89,52 MPa or about 51,45% from the allowable stress on the part where pipe start to bends. Variation on the value of installation parameters also changed the stress value. But the stress is still under the allowable stress except on the depth above 57,351 metres with the stress 175,54 MPa or 100,88% from the allowable stress. So it is better if we no install the pipe wth the depth more than 57.351 metres. As a suggestion, it is better to analyze the stress because the load from outside the pipe like the weight of the soil above the pipe.